2021
DOI: 10.1093/hmg/ddab006
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell ATAC-Seq reveals cell type-specific transcriptional regulation and unique chromatin accessibility in human spermatogenesis

Abstract: During human spermatogenesis, germ cells undergo dynamic changes in chromatin organization/re-packaging and in transcriptomes. In order to better understand the underlying mechanism(s), scATAC-Seq of 5376 testicular cells from 3 normal men were performed. Data were analyzed in parallel with the scRNA-Seq data of human testicular cells. In all, 10 germ cell types associated with spermatogenesis and 6 testicular somatic cell types were identified, along with 142 024 peaks located in promoter, genebody and CpG Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…Cell type–specific chromatin accessibility is involved in determining and maintaining cellular identity. 17,32 We measured chromatin accessibility of purified neonatal aCMs and vCMs in biological duplicate by ATAC-seq. There was high correlation between the replicate samples (Figure S8A; Extended Data 1 and 3); 59 939 accessible regions were reproducible across the 2 chambers; 4060 were atrium specific and 12 970 were ventricle specific (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Cell type–specific chromatin accessibility is involved in determining and maintaining cellular identity. 17,32 We measured chromatin accessibility of purified neonatal aCMs and vCMs in biological duplicate by ATAC-seq. There was high correlation between the replicate samples (Figure S8A; Extended Data 1 and 3); 59 939 accessible regions were reproducible across the 2 chambers; 4060 were atrium specific and 12 970 were ventricle specific (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…The role of engrailed 1 ( En1 , the most highly downregulated gene identified in our RNAseq analysis) in spermatogenesis has not yet been evaluated. However, a recent study showed that the EN1 motif is present at a high frequency in accessible regions of chromatin in human pachytene spermatocytes, but not in differentiating spermatogonia [ 62 ]. En1 regulation by CTNNB1 could therefore help reconcile the results of this study with the results obtained by Kumar et al [ 19 ], as stabilization of CTNNB1 would first antagonize SSC activity and promote entry of spermatogonia into meiosis, but would then block progression through later stages of meiosis by inhibiting En1 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, considerable efforts have been devoted to achieving better understanding of the molecular networks, regulatory programs, and germline-soma or soma-soma communications during gametogenesis and embryogenesis. In particular, the rapid advancement of highthroughput sequencing technologies and ultra-low-input (or even single-cell) omics approaches have accelerated novel discoveries in reproductive development e.g., (Wang et al, 2018;Qiao et al, 2020;Xu K. et al, 2021;He et al, 2021b;Tyser et al, 2021;Yan et al, 2021;Wu et al, 2022;Xiong et al, 2022). Towards this direction, Qian et al profiled the transcriptomes of 14,315 single testicular cells from adult zebrafish testes by single-cell RNA sequencing (scRNA-seq) using the 10x Genomics Chromium platform, identified ten distinguishable cell types with novelly revealed marker genes, and characterized interactions between somatic cells and germ cells through ligand-receptor analysis.…”
Section: Editorial On the Research Topic Reproductive Genomicsmentioning
confidence: 99%
“…Recently, considerable efforts have been devoted to achieving better understanding of the molecular networks, regulatory programs, and germline-soma or soma-soma communications during gametogenesis and embryogenesis. In particular, the rapid advancement of high-throughput sequencing technologies and ultra-low-input (or even single-cell) omics approaches have accelerated novel discoveries in reproductive development e.g., ( Wang et al, 2018 ; Qiao et al, 2020 ; Xu K. et al, 2021 ; He et al, 2021b ; Tyser et al, 2021 ; Yan et al, 2021 ; Wu et al, 2022 ; Xiong et al, 2022 ). Towards this direction, Qian et al .…”
mentioning
confidence: 99%